Strategi Intervensi Di SDN 16 Air Tawar - Destia Putri Cahyani (CV. ITTC INDONESIA, 2026)
This article aims to examine and explain the intervention strategies implemented at SDN 16 Air Tawar, with the goal of increasing the participation and empowerment of all school members. The underlying problem of this study is the lack of active participation of some school members in school activities and the underutilization of the potential and assets of teachers, educational staff, students, and parents. This study adopts a qualitative approach with a descriptive design. Data were obtained through observation, interviews, and documentation studies involving the principal, teachers, educational staff, students, and parent representatives. The research data revealed that an intervention approach emphasizing the empowerment of school assets, the maintenance of interpersonal relationships, and the strengthening of teamwork has the potential to strengthen a sense of belonging, collective responsibility, and collaboration among the school community. These findings indicate that participatory approaches and effective communication can build active engagement among school members. The conclusion of this study emphasizes that planned intervention strategies based on school needs contribute positively to improving the quality of school management and a supportive organizational atmosphere.